Application of transition metal dichalcogenides in mid‐infrared fiber laser. Issue 1 (6th November 2020) - Liu, Mengli; Liu, Wenjun; Liu, Ximei; Wang, Yaorong; Wei, Zhongming
Abstract: Due to the special working wavelength and superb beam quality, the mid‐infrared fiber laser has a wide application prospect in the fields of biomedicine, military defense, laser manufacturing, atmospheric detection, space communication, etc. In recent years, with the emergence of two‐dimensional (2D) saturable absorption materials, the development of mid‐infrared lasers ushered in new opportunities. In particular, as a potential 2D material, transition metal dichalcogenides (TMDs) with various types has attracted extensive attention from researchers because of its unique structural characteristics and ideal photoelectric performance. In this paper, the preparation, main properties and saturable absorption of TMDs are introduced in detail, and latest research progress of mid‐infrared lasers based on saturable absorbers at home and abroad is described. Abstract : As a potential 2D material, transition metal dichalcogenides (TMD) with various types have recently attracted extensive attention from researchers because of its unique structural characteristics and ideal photoelectric performance. Here, the preparation, main properties and application of TMDs as saturable absorbers in mid‐infrared lasers have become our research focus. The previous studies we reviewed indicate that TMDs has bright prospects in mid‐infrared lasers. Our review will not only help colleagues to clarify the application status of TMDs in mid‐infrared lasers, but also provide important enlightenment for the improvement scheme and future development direction of such lasers.